2017
DOI: 10.1093/ntr/ntx044
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Nicotine Delivery Systems (ENDS): Mapping the Indian Online Retail Market

Abstract: The study permits the use of web search engine to explore market availability of ENDS at various online retail websites. Recommendations from the study can be used to guide policy makers in developing strategies tailored to regulate availability and online sales of ENDS in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Of the eight articles, five articles were conducted in the United States, with the remaining three being conducted in China, Canada, and India, respectively. One study used qualitative methods (Cobb et al, 2015), three studies used quantitative methods (Grana & Ling, 2014; Hammond et al, 2015; Pulvers et al, 2017), and four studies used both quantitative and qualitative methods (Escobedo et al, 2018; Mohanty et al, 2017; Williams et al, 2018; Yao et al, 2016). All studies used a cross-sectional and observational study design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight articles, five articles were conducted in the United States, with the remaining three being conducted in China, Canada, and India, respectively. One study used qualitative methods (Cobb et al, 2015), three studies used quantitative methods (Grana & Ling, 2014; Hammond et al, 2015; Pulvers et al, 2017), and four studies used both quantitative and qualitative methods (Escobedo et al, 2018; Mohanty et al, 2017; Williams et al, 2018; Yao et al, 2016). All studies used a cross-sectional and observational study design.…”
Section: Resultsmentioning
confidence: 99%
“…All studies met the criteria on the data collection, data analysis, results, and discussion for the methodological quality evaluation (See Table 1 for details of included studies and Table 2 for methodology evaluations). One study did not clearly indicate whether they had a funding source or not (Mohanty et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Among the eleven member states in the WHO South-East Asia region; six countries namely North Korea, Nepal, Sri Lanka, Thailand, East Timor and India has banned e-cigarettes. In India, previously e-cigarettes are available in different flavours mostly through the online retail shopping websites [9]. One review published on vaping in India reported a total of 75 companies selling e-cigarettes online [10].…”
Section: Vaping In Who South-east Asia Region (Who-sear)mentioning
confidence: 99%
“…They purchase the products mostly from online retailers (57%) and street shops (53%) 8 . A study on online sales of ENDS, including e-cigarettes, electronic shisha, electronic hookah (e-hookah), and electronic cigars, in 2015, revealed that there were 65 different models of ENDS sold in Indian online market, of which 69% were flavoured, and only 26% displayed health warnings 9 . The availability of flavoured ENDS coupled with the limited health warnings featured in the product descriptions might encourage youth to experiment with ENDS/ENNDS, resulting in a new form of nicotine addiction.…”
Section: Introductionmentioning
confidence: 99%